2019
DOI: 10.1002/mats.201900025
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Specific Structure and Gas Permeability of Bromobutyl Rubber: A Combination of Experiments and Molecular Simulations

Abstract: The relationship between the specific structure and gas permeability of brominated poly(isobutylene‐co‐isoprene) rubber (BIIR) is investigated by a combination method of both experiments and molecular simulation. It is found that the various content of secondary allyl bromide isoprene (SABI) units exert an effect on transport behavior, including both diffusion and solution behavior of small molecule in BIIR, glass transition temperature, and vulcanization characteristics. The results show that a minimum value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…The oxygen permeability coefficient of the NR/TBIR vulcanizate with 20 phr TBIR content is the lowest value among these samples. The permeability coefficient is strongly affected by the diffusion coefficient (D) and solubility coefficient (S), and the corresponding value can be multiplied directly by the D and S. Generally, the diffusion coefficient and solubility coefficient represent the movement and interaction of the small molecules (O 2 in this work) in the polymer composites, respectively [32]. It is reported that there are several factors affecting the diffusion and solubility of the gas in polymers, such as the fraction free volume, cavitation, intermolecular interaction force, the mobility of the molecular chain, and so on [32].…”
Section: Oxygen Barrier Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…The oxygen permeability coefficient of the NR/TBIR vulcanizate with 20 phr TBIR content is the lowest value among these samples. The permeability coefficient is strongly affected by the diffusion coefficient (D) and solubility coefficient (S), and the corresponding value can be multiplied directly by the D and S. Generally, the diffusion coefficient and solubility coefficient represent the movement and interaction of the small molecules (O 2 in this work) in the polymer composites, respectively [32]. It is reported that there are several factors affecting the diffusion and solubility of the gas in polymers, such as the fraction free volume, cavitation, intermolecular interaction force, the mobility of the molecular chain, and so on [32].…”
Section: Oxygen Barrier Propertymentioning
confidence: 99%
“…The CED of NR, TPI, and TPB is about 289 MPa, 275 MPa, and 213 MPa, respectively [33]. The CED of NR is larger than TBIR due to the higher polarity brought about by polar substances such as protein in the NR [32]. TBIR, as reported, is a multiblock copolymer containing a block trans-structure of butadiene and isoprene [30].…”
Section: Oxygen Barrier Propertymentioning
confidence: 99%
“…Butyl rubber is prepared by the cationic copolymerization of isobutylene and isoprene (0.5–2.5 mol %). The incorporation of isoprene units provides butyl rubber with unsaturation, which allows for vulcanization and further postpolymerization functionalization. Despite the low unsaturation as compared to other synthetic rubbers such as butadiene rubber (BR), butyl rubber is widely used as an innerliner in tires and for pharmaceutical stoppers owing to its exceptional impermeability to gas resulting from the densely packed polymeric chains. , Meanwhile, in rubber compounding, fillers such as carbon black, clay, and silica are often added to reduce the cost and improve the physical properties of rubber compounds . The dispersion of fillers in a rubber compound plays an important role in the performance of a rubber product. , However, because of the nonpolar nature of butyl rubber, the dispersion of fillers, especially polar fillers such as silica, into the butyl rubber matrix is difficult .…”
Section: Introductionmentioning
confidence: 99%
“… 6 9 Despite the low unsaturation as compared to other synthetic rubbers such as butadiene rubber (BR), butyl rubber is widely used as an innerliner in tires 3 and for pharmaceutical stoppers 10 owing to its exceptional impermeability to gas resulting from the densely packed polymeric chains. 11 , 12 Meanwhile, in rubber compounding, fillers such as carbon black, clay, and silica are often added to reduce the cost and improve the physical properties of rubber compounds. 13 The dispersion of fillers in a rubber compound plays an important role in the performance of a rubber product.…”
Section: Introductionmentioning
confidence: 99%
“…However, IIR with higher isoprene (greater than 3.0 mol %) content has also been reported for some special applications . IIR is broadly used in adhesive, automotive, pharmaceutical, flexible electronics, and also in various other elastomeric applications. The exceptional air impermeability property of butyl rubber makes it an efficient candidate for the tire inner liner that holds the air tightly. Butyl rubber-based microporous materials are also used as a sorbent for the removal of oil spills and aromatic hydrocarbons from seawater. , Due to the very low level of unsaturation, butyl rubber shows superior oxidative and high chemical stability. As compared to other elastomers, IIR shows a relatively better damping property (high damping peak height and broad damping temperature range) which is due to the dense distribution of a large number of methyl side groups. …”
Section: Introductionmentioning
confidence: 99%